(untitled) (International Seven Journal of Multidisciplinary, 2024)
The National School Feeding Program - PNAE establishes criteria for the management of school feeding, the School Feeding Council, canteens and kitchens in schools and the work of nutritionists and educators in schools (CONCEIÇÃO, 2015; BRASIL, 2009a). In this sense, the PNAE, which was set up in 1955, is a public policy and aims to transfer financial resources to guarantee school meals for students in all basic education, early childhood education, secondary education and youth and adult education enrolled in public and philanthropic schools, to meet the nutritional needs of these students during their time in the classroom, contributing to their growth, development, learning and academic performance, and focuses on the formation of healthy eating habits (BRASIL, 2009b; CECANE PARANÁ, 2010). The consumption of vegetables is fundamental and should be part of any family’s menu. This is due to their nutritional value, which comes from the vitamins, minerals, fiber, low calorie intake and the fiber they contain (NASCIMENTO et al., 2005). It should be noted that the general population has changed its eating habits with regard to the consumption of fresh vegetables (OLIVEIRA et al., 2006). It should be noted, however, that vegetables eaten raw are responsible for the transmission of enteric diseases. Contamination occurs in the garden, through the use of inadequate irrigation water or fertilizers, during transportation or through handling at points of sale; and successive handling increases the chances of contamination (TAKAYANAGUI, 2001). This contamination is due to the presence of groups of coliforms, one of which is total coliform bacteria. The other group of fecal coliforms (coliforms at 45º C or thermotolerant) in food indicates the hygienic-sanitary conditions of the product and a better indication of the possible presence of enteropathogens (FRANCO; LANDGRAF, 2008). Concern about the quality and safety of food is a worldwide public health issue, due to the possibility of ingesting some type of food contaminated by pathogenic microorganisms (CUNHA, 2006). Vegetables that are eaten raw are likely sources of these microorganisms and should be considered in countries where sanitation is poor (ALMEIDA FILHO, 2008). The main objective of this study was to analyze the salads eaten raw by students, prepared in the Vitória da Conquista campus cafeteria, from a microbiological point of view.